Transformation of Consultation Services at P2TP2A: Case of Children Victims of Physical Violence - Raharjo, Agus; Muliani, Tri; Mulyono, Maulana Hadi (Institut Agama Islam Negeri Parepare, 2024)
This article evaluates the transformation of consultation services by the Integrated Service Center for the Empowerment of Women and Children (P2TP2A) in Malang City for child victims of physical violence. The research utilizes a mixed-methods approach with a descriptive quantitative and qualitative design. Quantitative data was collected through questionnaires measuring the stress levels and psychological recovery of children, while qualitative data was obtained through in-depth interviews with victims and counselors. The results indicate significant transformation in consultation services, particularly in the consistent implementation of SOPs. This is reflected in the reduction of stress, improved understanding of personal rights, better social behavior, and reduced aggressiveness in children. However, challenges such as limited session time and suboptimal family involvement still persist. The study concludes that the transformation of consultation services at P2TP2A Malang is effective in supporting the recovery of child victims of physical violence but requires further adjustments to address existing challenges. These findings are expected to serve as a reference for improving the quality of consultation services at P2TP2A and similar institutions.